2017
DOI: 10.1590/0001-3765201720170450
|View full text |Cite
|
Sign up to set email alerts
|

Pollen morphology and viability in Bromeliaceae

Abstract: Pollen morphology characterization is important in taxonomy, conservation and plant breeding, and pollen viability studies can support breeding programs. This study investigated pollen morphology and male fertility in 18 species of Bromeliaceae with ornamental potential. For morphological characterization, pollen grains were acetolyzed and characterization of exine was done using scanning and transmission electron microscopy. Pollen viability was investigated by in vitro germination and histochemical tests. Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 26 publications
2
23
0
1
Order By: Relevance
“…For each drop, we counted the pollen grains using the ‘scan’ technique (Caballero-Martínez et al 2009) and thus determined the frequency of bromeliad pollen. The bromeliad pollen could be easily distinguished from the pollen of other families present in the samples, but it is difficult with some genera at subfamily level (Silva et al 2016; Souza et al 2017). In this case, the only overlapping species from the same genus were both species of Werauhia , and no bat was captured at that moment.…”
Section: Methodsmentioning
confidence: 99%
“…For each drop, we counted the pollen grains using the ‘scan’ technique (Caballero-Martínez et al 2009) and thus determined the frequency of bromeliad pollen. The bromeliad pollen could be easily distinguished from the pollen of other families present in the samples, but it is difficult with some genera at subfamily level (Silva et al 2016; Souza et al 2017). In this case, the only overlapping species from the same genus were both species of Werauhia , and no bat was captured at that moment.…”
Section: Methodsmentioning
confidence: 99%
“…Investigations of pollen morphology are important to support taxonomic (Khan et al, 2019; Majeed et al, 2020; Nazish et al, 2019) and conservation studies and to choose species for controlled crosses in genetic improvement programs aimed to obtain promising hybrids (Silva, Ribeiro, Luizi‐Ponzo, & Faria, 2016; Souza, Souza, et al, 2017). Recent research has shown that micromorphological traits observed by light microscopy (LM) and scanning electron microscopy (SEM) provide more detailed knowledge of the morphology of pollen grains, contributing to the identification, classification and delineation of the species belonging to different families, such as Caryophyllaceae (Cui, Hu, Ren, & Liu, 2020; Ullah, Zafar, et al, 2018; Ullah, Zaman, et al, 2018), Lamiaceae (Gul et al, 2019), and Melanthiaceae (Hu, Zhao, Zhao, & Liu, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been published describing the pollen morphology and ultrastructure of Bromeliaceae species, such as Ehler and Schill (1973), Erdtman and Praglowski (1974), Roubik and Moreno (1991), Wanderley and Melhem (1991), Halbritter (1992), Halbritter and Till (1998), Tardivo and Rodrigues (1998), Vervaeke, Parton, Deroose, and De Proft (2003), Souza, Mendonça, and Gonçalves‐Esteves (2004), Moreira, Cruz‐Barros, and Wanderley (2005), Soares, Souza, Rossi, and Souza (2011), Silva et al (2016), Souza, Souza, et al (2017), Santos, Versieux, Wanderley, and Luz (2018), Schroeder, Junior, Dec, and Mouga (2019), and Santos, Wanderley, Versieux, and Luz (2020). However, due to the size of the family, these studies are insufficient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other difficulties may be related to problems in the meiotic and post-meiotic behavior of these hybrids, which can generate plants of little or no agronomic value, with low fertility or sterility due to reduction in the production of viable pollens and seeds. Thus, the evaluation of pollen viability is essential for the success of interspecific crosses (Pagliarini, 2000;Souza et al, 2017), including Jatropha species. In addition, Genomic In Situ Hybridization (GISH) studies of interspecific hybrids can provide relevant information for breeding programs, allowing differentiation of the parental genomes in hybrid cells and the detection of non-homologous recombination, which is fundamental for the introgression of new traits into material derived from interspecific hybrids.…”
Section: Introductionmentioning
confidence: 99%